Plasmon resonance as a new effective approach for controlled radical generation - Votkina D. E. Darjya Evgenjevna; Petunin P. V. Pavel Vasilievich; Guselnikova O. A. Olga Andreevna; Marque S. R. A. Sylvain; Postnikov P. S. Pavel Sergeevich (2023, 2023)
Title screen